How did the Recession Change the Communication of Corporate Social Responsibility Activities?. Issue 2 (April 2015) - Green, Todd; Peloza, John
Abstract : One key objective of corporate social responsibility (CSR) activities is the enhancement of relationships with stakeholders such as consumers. However, in order for firms to enhance stakeholder relationships, individuals must be made aware of firms' CSR activities. As a result, firms dedicate considerable resources to CSR-related advertisements. The current research proposes that, during recessionary periods, managers alter their CSR communications in response to perceived consumer retrenchment to purchase criteria such as price and quality. Using sensemaking as a framework, we predict that managers used cues from consumers during the recent recession, to alter their CSR communications strategies accordingly. We test our hypotheses through a content analysis of over 4000 print advertisements from 2006 to 2010. Our findings demonstrate that instead of lower levels of CSR communications during the recession, the odds of an advertisement containing CSR messages actually increased during the recession. However, the content of this advertising did change in concert with the sensemaking hypotheses. Specifically, during periods of economic decline, CSR messages were more likely to be integrated into "mainstream" advertising. We also find that the use of self-oriented appeals (e.g., cost savings due to energy efficiency) sharply increased during the period of economic decline. We highlight how managers can use these findings to increase the probability that CSR communications will deliver the expected relational benefits with consumers.